2021
DOI: 10.7759/cureus.17635
|View full text |Cite
|
Sign up to set email alerts
|

Post-Operative Splinting Versus Casting of Pediatric Supracondylar Humerus Fractures

Abstract: Background Supracondylar humerus fractures (SCH) are common upper extremity fractures in children and are usually treated by closed reduction and percutaneous pinning. Post-operative management may cause complications, but the difference between cast and splint has not been closely investigated. Purpose Our objective was to compare casting and splinting of SCH fractures with respect to post-operative complications. Patients and methods We reviewed 1,146 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…A recent Cochrane review into supracondylar treatments, unfortunately, did not investigate this, likely a reflection of the paucity of evidence in this area, and a study by Lee and colleagues in 2021 comparing complication rates of pinned supracondylar fractures immobilized postoperatively in splint versus cast failed to comment on the length of time immobilized between the two groups, again likely highlighting the large variation in these data. 12,13 In a recent paper by Pavone et al, 14 outlining results from a survey of the members of the European Paediatric Orthopaedic Society, almost the entire sample of 184 members declared that pins should be removed between 3 and 4 weeks postoperatively, but there was no indication regarding the period of immobilization, or if there needs to be any further immobilization after pins are removed. Sheikdon et al 15 in 2022 suggested that prolonged immobilization of these fractures for 6 weeks postoperatively rather than 4 was significantly associated with unsatisfactory functional management outcomes of a range of motion and carrying angle at 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent Cochrane review into supracondylar treatments, unfortunately, did not investigate this, likely a reflection of the paucity of evidence in this area, and a study by Lee and colleagues in 2021 comparing complication rates of pinned supracondylar fractures immobilized postoperatively in splint versus cast failed to comment on the length of time immobilized between the two groups, again likely highlighting the large variation in these data. 12,13 In a recent paper by Pavone et al, 14 outlining results from a survey of the members of the European Paediatric Orthopaedic Society, almost the entire sample of 184 members declared that pins should be removed between 3 and 4 weeks postoperatively, but there was no indication regarding the period of immobilization, or if there needs to be any further immobilization after pins are removed. Sheikdon et al 15 in 2022 suggested that prolonged immobilization of these fractures for 6 weeks postoperatively rather than 4 was significantly associated with unsatisfactory functional management outcomes of a range of motion and carrying angle at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of immobilization following reduction and K-wire fixation of displaced supracondylar fractures is variable among different surgical centers worldwide, and due to the lack of trials investigating this, there remains no evidence-based recommendation. A recent Cochrane review into supracondylar treatments, unfortunately, did not investigate this, likely a reflection of the paucity of evidence in this area, and a study by Lee and colleagues in 2021 comparing complication rates of pinned supracondylar fractures immobilized postoperatively in splint versus cast failed to comment on the length of time immobilized between the two groups, again likely highlighting the large variation in these data 12,13 . In a recent paper by Pavone et al, 14 outlining results from a survey of the members of the European Paediatric Orthopaedic Society, almost the entire sample of 184 members declared that pins should be removed between 3 and 4 weeks postoperatively, but there was no indication regarding the period of immobilization, or if there needs to be any further immobilization after pins are removed.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown no difference in unscheduled returns or secondary displacement with splinting versus casting. 37,38 The author has had good success with ∼10 layers of plaster for a posterior splint supplemented with a ∼5-layered lateral slab to cover pins, with an ACE wrap applied directly onto the plaster while drying to make it harder to remove.…”
Section: Surgical Carementioning
confidence: 99%